Measuring Inclusive Education in Portuguese Schools: Adaptation and Validation of a Questionnaire - Carvalho, Marisa; Cruz, Joana; Azevedo, Helena; Fonseca, Helena (Frontiers in Education, 2022)
In the last decades, the debate about inclusive education has gained considerable attention in policy, research, and practice. Therefore, there is also a growing interest in assessing how inclusive education is taking place in schools. Self-assessment and self-reflection tools are strategic to examine schools' inclusion and to guide needed changes. This study is an attempt to provide Portuguese schools with self-assessment tools for improvement. Themis Inclusion Tool was translated and adapted into a Portuguese version named Resources and Practices for Inclusive Education and evaluated the instrument's psychometric structure. A web survey was completed online by 924 participants. An EFA suggested two different factors: Inclusive Resources, human, technical and technological resources used to promote learning and; Inclusive Practices, beliefs and behaviours that can be implemented to promote learning. These two factors were supported by confirmatory analysis. Overall, the Resources and Practices for Inclusive Education presented a robust factorial structure and good psychometric properties, appearing to be a valid and reliable measure for assessing inclusive education in Portuguese schools.